Determination of Thermal Expansion, Defect Formation Energy, and Defect-Induced Strain of α-U Via ab Initio Molecular Dynamics - Beeler, Benjamin; Mahbuba, Khadija; Wang, Yuhao; Jokisaari, Andrea (Frontiers in Materials, 2021)
Uranium (U) is often alloyed with molybdenum (Mo) or zirconium (Zr) in order to stabilize its high-temperature body-centered cubic phase for use in nuclear reactors. However, in all metallic fuel forms, the alpha phase of U remains in some fraction. This phase decomposition due to temperature or compositional variance can play an outsized role on fuel performance and microstructural evolution. Relatively little is known about fundamental point defect properties in alpha-U at non-zero temperatures, from either computational or experimental studies. This work performs the first thorough evaluation of the alpha phase of U via ab initio molecular dynamics (AIMD). A number of thermophysical properties are calculated as a function of temperature, including equilibrium lattice parameters, thermal expansion, and heat capacity. These results indicate a two-region behavior, with the transition at 400 K. The thermal expansion expansion/contraction in the a/b direction occurs rapidly from 100 K up to 400 K, after which a more linear and gradual change in the lattice constant takes place. The volumetric expansion matches experiments quantitatively, but the individual lattice constant expansion only matches experiments qualitatively. Point defect formation energies and induced lattice strains are also determined as a function of temperature, providing insight on defect populations and the fundamentals of irradiation growth in alpha-U. Interstitials induce significantly more strain than vacancies, and the nature of that strain is highly dependent on the individual lattice directions. The direction of point defect induced lattice strain is contrary to the irradiation growth behavior of alpha-U. This work shows that isolated point defects cannot be the primary driving force responsible for the significant irradiation induced growth of alpha-U observed experimentally.